A geographical cline in craniofacial morphology across populations of Mesoamerican lake‐dwelling fishes. Issue 3 (5th January 2020) - Powers, Amanda K.; Garita‐Alvarado, Carlos A.; Rodiles‐Hernández, Rocío; Berning, Daniel J.; Gross, Joshua B.; Ornelas‐García, C. Patricia
Abstract: Together, the complex geological history and climatic diversity of Mesoamerica create a rich source of biodiversity from which evolutionary processes can be studied. Here, we discuss highly divergent morphs of lake‐dwelling fishes distributed across Mexico and Central America, originally recognized as members of different genera ( Astyanax and " Bramocharax") . Recent phylogenetic studies, however, suggest these morphs group within the same genus and readily hybridize. Despite genetic similarities, Bramocharax morphs exhibit stark differences in cranial shape and dentition. We investigated the evolution of several cranial traits that vary across morphs collected from four lakes in Mexico and Nicaragua and discovered an ecomorphological cline from northern to southern lakes. Northern populations of sympatric morphs exhibit a similar cranial shape and tooth morphology. Southern populations of Bramocharax morphs, however, showed a larger disparity in maxillary teeth, length and frequency of unicuspid teeth, an elongated snout, and a streamlined cranium compared to Astyanax morphs. This divergence of craniofacial morphology likely evolved in association with differences in trophic niches. We discuss the morphological differences across the four lake systems in terms of geological history and trophic dynamics. In summary, our study suggests that Bramocharax morphs are likely locally adapted members derived from independent Astyanax lineages, highlighting an interesting parallel evolutionary pattern within the Astyanax genus. Abstract : Distribution of Astyanax and Bramocharax morphs across four Mesoamerican lakes. The Astyanax genus comprises fish species widely distributed across Mexico and Central America. Lake‐dwelling morphs demonstrate genetic similarity, but morphological differences in craniofacial and body shape. Here, we characterize wild‐caught Astyanax and Bramocharax morphs from four lakes: two Mexican lakes (Catemaco and Ocotalito; green) and two Nicaraguan Lakes (Managua and Nicaragua; orange). Research Highlights: We characterized the evolution of cranial traits in two divergent lacustrine morphs in Astyanax genus from four lakes in Mesoamerica. We recovered an ecomorphological disparity cline from northern to southern lakes. Bramocharax morphs showed a convergent cranial traits in Mesoamerican lakes.